Tax Obedience During COVID Times: A Role-Play Illustrating Tax Policy Dilemmas - Nellie Munin; Yael Efron (Washington University Journal of Law and Policy, 2024)
Professors at Zefat Academic College (ZAC) School of Law in Israel are engaging students with innovating pedagogical techniques in tax law instruction. Societal and educational challenges caused by the global COVID-19 pandemic shifted the professors’ focus from transferring knowledge and information to developing innovating learning methods and practicing skills. The professors have designed and implemented a role play to illustrate universal challenges of tax avoidance faced by tax regimes globally caused by the economic impact of COVID-19. This article describes the simulation, the considerations underlying its design and conduct, as well as the analysis of its didactic value, in light of relevant literature. The authors posit that students in the modern classroom are better served when students engage in simulations that explore the theoretical underpinnings of legal frameworks by requiring practical application to real world issues. In doing so, the professors have crafted a pedagogical approach that challenges students critically approach and apply their newfound understanding of policy choices, political and economic interests, as well as social, economic, and political implications of tax laws.
Keywords: TaxLawEducation; InnovativePedagogy; RolePlayLearning; LegalSimulations; COVID19Impact